A Midsummer Night's Dream : And Other Stories From Shakespeare's Plays - Shakespeare, William, 1564-1616; Edited by Foulds, David (Oxford Oxford University Press, 2005)
One midsummer night, two lovers run away to the wood. There they find two other lovers - but what they don't know is that the wood is full of magical people: the fairies and elves. When a naughty elf decides to play a trick, everything becomes very mixed up. The four stories in this book are about things becoming mixed up
Include Color Illustration
Keywords: New literates, Writing for